NIGELLA SATIVA AND ITS ACTIVE CONSTITUENTS THYMOQUINONE SHOWS PIVOTAL ROLE IN THE DISEASES PREVENTION AND TREATMENT - H Rahmani, Arshad; Aly, Salah M (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Medicinal plants and its constituents used as therapeutics drugs in the health management since ancient time and large population of the world relies on traditional medicine for primary health treatment. However, medicinal plant has opened a new window of research in diseases prevention and treatment due to safe, affordable and easy to access properties. In this vista, Nigella sativa (NS) are commonly used as traditional medicines worldwide in the disease prevention due to less side-effect and affordable properties. NS and its constituents are a rich source of antioxidant, an influential free radical scavenger and also modulator of various biological activities. In this review, we summarized the therapeutics effects of black seed and its constituents in the diseases treatment and prevention through modulation of antioxidant, anti-inflammatory, anti-tumor, hepato-protective and other genetic activities. Keywords: Nigella sativa, Therapy, Genetic activities, Antioxidant.